A density functional theory evaluation on silicon doped boron nitride nanocones: ibuprofen drug sensing characterisation. Issue 15 (12th October 2020) - Zuo, Xia; Geng, Lijuan; Gao, Hongzhu; Liu, Bensheng; Wu, Liang
ABSTRACT: Calculations based on the first principle density functional theory have been performed to evaluate the electrical response of Si-doped and pristine boron nitride nanocones (BNNCs) to ibuprofen (IBP) drug sensor at room temperature. The adsorption of IBP causes a significant decrease in the Si-doped BNNCs Eg (from 4.60 to 3.31 eV), thereby, the electrical conductivity has also increased. While the Eg value of pristine BNNCs was reduced slightly after IBP adsorption. It indicates that the Si-doped BNNCs compared to pristine state could be an appropriate candidate for IBP detection and may be used in the electronic sensors. Furthermore, the work function of Si-doped BNNCs is influenced by the IBP adsorption and the work function of doped and pristine BNNCs are reduce about 17.09% and 13.97%, respectively. It could also be a work function based sensor for the detection of IBP. The Si-doped BNNCs have also the advantage of short recovery time about 37.58 ms for desorption of IBP.